2015
DOI: 10.4084/mjhid.2015.034
|View full text |Cite
|
Sign up to set email alerts
|

Rare Cytogenetic Abnormalities in Myelodysplastic Syndromes

Abstract: The karyotype represents one of the main cornerstones for the International Prognostic Scoring System (IPSS) and the revised IPSS-R (IPSS-R) that are most widely used for prognostication in patients with myelodysplastic syndromes (MDS). The most frequent cytogenetic abnormalities in MDS, i.e. del(5q), -7/del(7q), +8, complex karyotypes, or −Y have been extensively explored for their prognostic impact. The IPSS-R also considers some less frequent abnormalities such as del(11q), isochromosome 17, +19, or 3q abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Isolated deletion 5q was seen only in a single female patient who presented as refractory anemia. Numerical gain of chromosome 11 a rare cytogenetic finding in MDS is also observed in one case [11]. Other cytogenetic findings are mentioned in Table 5.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Isolated deletion 5q was seen only in a single female patient who presented as refractory anemia. Numerical gain of chromosome 11 a rare cytogenetic finding in MDS is also observed in one case [11]. Other cytogenetic findings are mentioned in Table 5.…”
Section: Resultsmentioning
confidence: 89%
“…Median progression free survival of all followed up cases is 1.5 months for very high risk, 6 months for high risk, 13 (Figure 2). Disease specific treatment was chosen by only 26 (50%) patients due to availability of resources out of which 1 (3.8%) was very low risk, 9 (34.6%) were low risk, 11 …”
Section: Follow Up Outcome and Mortalitymentioning
confidence: 99%
“…Moreover, according to multicentric cytogenetic studies, trisomy 13 was observed in 0.2% patients, detectable as an single aberration, or combined with an additional abnormality [20]. A sufficient gender imbalance was reported for this condition (21 males of 27 cases).…”
Section: Introductionmentioning
confidence: 95%
“…Translocation 11q23/MLL is another very rare occurrence in primary MDS, with the overall survival being about 26 months and the risk to develop acute leukemia being up to 40% within a one-year interval and up to 92% within a five-year period. Loss of one X chromosome in women is a rare abnormality in MDS and AML: it occurs in 0.2–0.3% of cases and in up to 1.5% of patients who combine these conditions with other abnormalities and is characterized by a median overall survival of ~6 months [ 89 ]. The presence of translocation 1q in three patients originally diagnosed with MDS, which later evolved to AML, has been reported [ 90 ].…”
Section: Prognostic Systems For Mdsmentioning
confidence: 99%